Diversidad y distribución geográfica del salivazo (homoptera: Cercopidae) asociado con gramíneas en Colombia y Ecuador - Peck, DC (2001)
The diversity and geographical distribution of spittlebugs (Homoptera: Cercopidae) associated with wild and cultivated graminoids [Poaceae] were studied to obtain new information on the distribution, host plants and nomenclature of some economically important species. Data were obtained for 21 of the 32 Colombian departments and 9 of the 20 Ecuadorian provinces. The presence of 15 species in Colombia and 8 species in Ecuador was confirmed. These totalled to 18 species from 7 genera: Aeneolamia, Isozulia, Mahanarva, Notozulia [Zulia], Prosapia, Sphenorhina and Zulia. A change in nomenclature was found for Z. carbonaria, incorrectly known in Colombia as Z. colombiana. Seven species were reported for the first time in Colombia. Two of these are new species: Mahanarva sp. nov. from the Amazonia of colombia and Ecuador and coastal Ecuador and Zulia sp. nov. from the Pacific Coast of Colombia and Ecuador. Another species, N. entreriana [Z. entreriana] in the Department of Meta, represents a possible introduction from Brazil, and the species P. simulans in the Department of Valle del Cauca represents a possible new invasion from Central America. The host list for Colombia and Ecuador included 26 species of graminoids. Host plants, distribution at the level of country, department and province, and taxonomic notes are summarized for each spittlebug species. The implications of diversity for pest management is discussed.